The Truth of the Hadith about the Reasons for the Revelation of Surah Al-Kāfirūn and Its Effect on Religious Tolerance - Rohmansyah Rohmansyah (Diroyah : Jurnal Studi Ilmu Hadis, 2022)
Hadith’s authenticity on crucial things, such as tolerance in Surah Al-Kāfirūn, must be studied. This paper aims to reveal and prove the status of the hadith as evidence of the revelation of Surah Al-Kāfirūn, associated with religious tolerance. This study belongs to library research implementing a descriptive-analytic approach and a theoretical framework of the Sociology of Knowledge by Peter L Berger and Thomas Lukmann. The results unveiled that the hadith concerning the revelation of Surah Al-Kāfirūn cannot be used as evidence because it was daif and mawquf. However, the tacitan of the hadith did not weaken the validity of the surah, of which the status is the word of God, which is qaṭ’ī. Therefore, Al-Kāfirūn’s correlation with religious tolerance remains valid as long as it pays attention to the determined limits. Mutual respect, assistance, and cooperation among religious people of different beliefs, and things unrelated to ideological aspects such as aqidah, worship, and sharia must be considered.The descent of surat  al-Kāfirun  exerts a  considerable influence on  the religiousness of the people. Every human being is  free  to choose his religion  according to his beliefs  and their own beliefs. But especially Muslims  have  rules  that  stick  to their religion, as well as  non-Muslims. Mereka is  free  to perform  worship  according to his understanding  and  belief. Surat al-Kāfirūn  in addition to  teaching plurality  in  religion  also  teaches the attitude of maintaining  unity  and unity of  the people,  reducing  hostility  and  eliminating  violence  and panatic  against  other groups. The majesty of  surat  al-Kāfirūn became a  way  out of the problem  of  conflict  between  religious  people  since its descent  until  now so that  between  religious  people  live get along well  and  don't  bother each other.